The Proceedings of the Second ICST International Conference on Pervasive Computing Technologies for Healthcare 2008
DOI: 10.4108/icst.pervasivehealth2008.2526
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Long Term Variations of Heart Rate Variability in Subjects with Higher Self Reporting Stress Scores

Abstract: Heart rate variability (HRV) has been well established to measure instantaneous levels of mental stress. Circadian patterns of HRV features have been reported but their relationships to mental stress were not studied explicitly for estimating stress levels. In this study, we investigated long term variations of HRV features to provide a reliable measure of chronic stress levels. Twenty three subjects were divided into high (n=10) and low stress group (n=13) depending their selfreporting stress scores. HRV feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Subjects were divided into high and low stress group based on their self reporting stress scores (stress response inventory) [18] and their HRV features were measured at multiple time points [19]. In this study, short term analysis has been performed for heartbeat data obtained at five different time points from two subject groups.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects were divided into high and low stress group based on their self reporting stress scores (stress response inventory) [18] and their HRV features were measured at multiple time points [19]. In this study, short term analysis has been performed for heartbeat data obtained at five different time points from two subject groups.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that a minimum of 60 seconds ECG signal is needed for stress detection [2][4][5] [13][17] [18]; however, in our study, we attempted to show that a 30 sec long ECG signal is sufficient for stress analysis. To generate RR-intervals from the ECG signal, we performed the following steps: 1) applied Butterworth bandpass filter [0.2Hz to 5Hz] to filter low and high frequency components ( Figure Then for each RR-interval, 103 HRV features suggested by Boonnithi and Phongsuphap [4] were computed using the HRVAS software [15].…”
Section: Data Processingmentioning
confidence: 92%
“…Recent work has shown that some of the HRV features can potentially be used for distinguishing a subject's normal mental state from a stressed one [4], [13] & [14]. Besides many civilian applications of detecting and monitoring disease processes [1], HRV might also be relevant to security and military applications such as: border patrol, stress detection for deception [3], [17], and Wounded-Warrior triage [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations